Evaluasi Kinerja Keuangan Daerah Kota Bandung Tahun Anggaran 2010-2014 - Sukardi, Agung Slamet, Siti Fatimah Nurhayati,SE, M.Si (2014)
This research is a descriptive study describing and analyzing the data obtained. The object of this research is the Government of Bandung with the title "Performance Evaluation of Local Government Finance Anggran Bandung Year 2010-2014". Analyzer used to measure the performance of the financial management of the area the city is the area of financial independence ratio, the ratio of the area of financial dependency, the ratio of the degree of fiscal decentralization and effectiveness ratio and for mapping regional financial indices using Growth, Share and elasticity. The results of the analysis of the calculation of the ratio during the period of 2010-2014 diperleh hasi. The level of financial independence Bandung city area showed an average sebear 63.29%, so the city of Bandung sign kalam category sanggat less. The level of financial dependence region showed an average of 46.86%, sehinggan entered the high level of dependency. The degree of fiscal decentralization gained an average of 28.15%, so the city government into the category of being. The level of effectiveness of local revenue earned an average of 113.21% in the category very effective. From the calculation of the financial performance of the index (CCI) and the quadrant method mmenunjukan financial capability index calculation results Bandung fiscal year 2010 through 2014, the scale index indicates the number 62.736. This means that the financial capacity of the city of Bandung is high. From the calculation of the share and the growth of the budget summary income and expenditure Bandung fiscal year 2010 through 2014, the obtained data is a share of 59.926% and a growth of 58.983%. Further mapping of regional financial capability based on the quadrant method. The position of the city of Bandung is in quadrant II. These conditions have not been ideal, but the region has the potential pegembangan. Keywords: self-sufficiency ratio, the dependency ratio area, the ratio of decentralization